MEDIA SOSIAL DAN GLOBALISASI INFORMASI: STUDI KASUS PERINGATAN DARURAT GARUDA BIRU OLEH NAJWA SHIHAB - Riyadi; Aziz, Syamsuddin; Marsuki (NIVEDANA : Jurnal Komunikasi dan Bahasa, 2025)
This study analyzes the impact of Najwa Shihab's "Peringatan Darurat Garuda Biru" post on public opinion, political discourse, and government policies in Indonesia following the 2024 elections. Focusing on criticisms of political dynasties and the dominance of mainstream media narratives, the study demonstrates how social media can serve as a critical tool in promoting transparency, accountability, and active citizen participation in democracy. Using a qualitative literature review approach, the study finds that the post effectively mobilized large-scale public opinion, creating significant pressure on the government to act with greater transparency and accountability. Furthermore, the post successfully broadened critical discussions within society. However, its long-term effectiveness is hindered by opinion polarization and the influence of digital media algorithms. These findings offer practical benefits by highlighting the importance of combining digital mobilization with tangible actions to enhance democratic quality. The study also raises awareness about challenges in digital public spaces, enabling citizens to approach digital information more critically and thoughtfully.